Educação profissional técnica de nível médio na modalidade de educação de jovens e adultos: uma reflexão sobre a prática pedagógica docente - Duarte, Tayna Bento de Souza (2019)
The Technological High School Education Program (EPTNM), implements the study program called Youth and Adult Teachings (EJA). This study program is part of the Brazilian National Integration Program for Professional and Basic Education from Youth and Adult Teachings (PROEJA). This government education program aims to increase the professional scholarity, by setting up new standards for the teacher’s education know-how, which must be orchestrated with the courses expertises proposals. At this context, the teachers education know-how refers to theoretical and practical activities, with assessments between the teachers. This research was accomplished at Graduate Professional and Technological Education Program (ProfEPT), and engaged on a research group, name Control and Management from Pedagogical Clearances on Professional and Technological Education. The main goal of this research is to analyze how the theoretical intercessions from EPTNM acts in EJA, according to the continuous undergraduate program, with the problematization teaching methodology, which allouds the teacher to have a syntonized feedback of the education process, building a live loop classroom dynamics. The research workshops were hold on the Federal Institute of Amazonas (IFAM), Manaus’ City Center Campus (CMC), and the participants were the teachers from the Mechanical High School Undergraduate Program from the daytime shift of EJA. The qualitative approach was used, according to the Action Research method and the main result was a continuous educating workshop, constructed with the problematization methodology in consonance with the Arch of Manguerez. The concepts of the Arch encompass, objectives, concepts and principles to justify the EPTNM’s courses proposals from PROEJA. The Workshops were divided in stages, each stage is an important part of the framework methodology, and these requirements were looking forward to the teacher’s reflexive práxis, aiming the changing processes on the classroom standards. The pedagogical teaching práxis on EJA, presenting new perspectives to the teacher’s labor, accomplishing knowledge from student rights in different ages on the study program. The most feasible result is the educational product, reconstructing scenarios to represent the core of the Arch of Manguerez approach, implementing formative procedures on a live experience environment, with a unified and collaborative ambience.